Efficacy of Continuation/Maintenance Electroconvulsive Therapy in the Treatment of Patients With Mood Disorders: A Retrospective Analysis. Issue 2 (June 2019) - Hausmann, Armand; Post, Thomas; Post, Fabienne; Dehning, Julia; Kemmler, Georg; Grunze, Heinz
Abstract : Objective: The aim of the study was to contribute evidence for the efficacy of continuation and maintenance electroconvulsive therapy (c/mECT) going beyond the existing literature by examining longer-term outcomes from a single center. Methods: We conducted a retrospective observational cohort study for a 14-year period, in which a group of 27 individuals with mood disorders, as defined by International Classification of Diseases-10, were examined and received acute ECT, followed by c/mECT. Mirror-image comparison of individual data sets, 5 years before and after c/mECT, was conducted for the number and mean duration of hospitalizations, as well as inpatient days per year. Statistical analysis was performed using general equation estimation modeling. Results: In 27 patients (63% female, mean ± SD age = 54.3 ± 11.7 years) experiencing either from bipolar (41%) or unipolar (59%) mood disorder, with most patients presenting with a depressive episode at hospital admission (93%), c/mECT was initiated after a successful course of acute ECT in addition to treatment as usual. In a 5-year period before and after starting c/mECT, we observed a significant decline in the mean number of hospitalizations per year (0.64 vs 0.32, P = 0.031), the average number of inpatient days per year (23.7 vs 6.1 days, P < 0.001), and the mean duration of hospital stays (41.6 vs 22.1 days, P = 0.031). Conclusions: The findings provide further support for the efficacy of c/mECT as an augmentation therapy to psychopharmacological treatment in patients experiencing mood disorders, who have responded to acute ECT. Further studies, however, using a controlled study design and larger sample sizes are needed.